Exploring the Present Through the Lens of the Past: A Comparative Analysis of Yo soy Lorenzo and Hijos del Desierto - Alejandro Bruna; Juan Pablo Sánchez Sepúlveda (Les Cahiers ALHIM)
This research investigates the phenomenon of historical discourse in period telenovelas in Chile, exploring how these television productions address contemporary issues. Semi-structured interviews were conducted with screenwriters and script team leaders to understand how the present and contemporary themes are intertwined in period narrative. The results show that period telenovelas do not fictionalize the present through a historical setting, but rather explore the elements that connect the past with the present, highlighting timeless social and political problems that are still current in Chilean society. The analysis of the telenovelas Yo soy Lorenzo, set in the 1960s, and Hijos del Desierto, set in the 1930s, reveals how current themes and historical narrative intertwine to offer a reflection on Chilean society through the lens of the past, helping educate the citizenship in relevant current affairs.